(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
Scaffolds for cell growth have been irreplaceable in regenerative medicine. Typically, the scaffold structures are rigid or semi-rigid. This can be overcome using multiphoton laser lithography that allows the fabrication of flexible geometries, appropriate for soft tissue application. A step beyond that is the application of a postprocessing step appropriate to hybrid polymers that results in new materials and new properties. This gives an option to produce new types of structures.